The Conceptualization, Perceptions, and Practice of Positive Education in University Student Accessibility Departments - KARAKI, SUHA (2023)
Recent studies have started moving the focus of academic contexts from mere achievement to the emphasis on wellbeing and positive psychology. Schools and universities are the main setting where students are prepared for their future, flourish and develop both mentally and academically. The field of education is witnessing a move towards a positive education model that encompasses skills students need in their life and the real world. The model enables learners to: become more aware of their abilities and self-worth, understand the need to be more engaged with themselves and others, and develop an ability to improve on the psychological and academic levels. The United Arab Emirates (UAE) is striving towards implementing a positive education model and positions education as a key element in measuring the nation’s success. It is aiming to be the happiest country in the world; accordingly, the government and its educational entities are launching positive education and mental health initiatives, networks and workshops. More importantly, the UAE is prioritizing its fully inclusive educational system that accentuates the need for right-based education and learner support. To that end, educational policies emphasize that students of all educational needs are taking an integral part in teaching and learning and are being prepared for a future of achievement and wellbeing. With the UAE underlining inclusive education and positive education, this study aims at investigating: 1) how positive education is conceptualized and implemented in student accessibility departments at a federal university in the UAE, 2) what the perceptions of relevant stakeholders are about positive education, and 3) what model/framework can be proposed to better comprehend and implement positive education. An exploratory sequential mixed-method approach was utilized through the use of triangulation and by means of: document analysis, observations, interviews, surveys and focus groups. The PERMA model which underlines positive emotion, engagement, relationships, meaning and accomplishment was used as the conceptual framework. Data analysis showed that although these five elements are prevalent in the accessibility department efforts, there is still a need for this positive education model to be institutionalized and documented to promote practical implementation and sustainability. This is further supported by literature that states that in spite of the increasing attention toward the growth of positive education, there is still a need to: understand how they are to be implemented in inclusive higher education settings, and to incorporate this educational framework in a more systematic and overt manner. This emphasizes the significance of this study, since it provides suggestions for a relevant framework that can be used in student accessibility departments in higher education through uncovering conceptualization, practice and perceptions of positive education.